La comunicación para el desarrollo en el marco del Buen Vivir. análisis de las estrategias de comunicación del Ministerio de Agricultura, Ganadería, Acuacultura y Pesca (MAGAP) durante el período 2016-2017. - Morán Gaibor, Mayra Fernanda. (2019)
This research studies the formulation of Communication for Development plans in government entities of Ecuador, within the Good Living paradigm, through the experience of the Ministry of Agriculture, Livestock, Aquaculture and Fisheries and its "Strategic planning of territorial intervention with a Participatory Communication and Development approach "(MAGAP, 2016). The results of the analysis show a lack of knowledge regarding Communication for Development, in the discourse and participation of those responsible for the elaboration of this strategy, which in its attempt to break with the institutional approach of the communicational work does not succeed in coming up with the proposals of a communication created from and for rural communities. In addition, we observe the absence of regulatory frameworks that regulate and guarantee the application of communication plans, in which aspects of participation, inclusion and democratization prevail, over diffusionist models. Something that does not necessarily coincide with the premises enunciated from the Good Living paradigm.